1979
DOI: 10.1172/jci109464
|View full text |Cite
|
Sign up to set email alerts
|

Role of Glucagon, Catecholamines, and Growth Hormone in Human Glucose Counterregulation

Abstract: A B S T R A C T To further characterize mechanisms of glucose counterregulation in man, the effects of pharmacologically inducd deficiencies of glucagon, growth hormone, and catecholamines (alone and in combination) on recovery of plasma glucose from insulin-induced hypoglycemia and attendant changes in isotopically ([3-3H]glucose) determined glucose fluxes were studied in 13 normal subjects. In control studies, recovery of plasma glucose from hypoglycemia was primarily due to a compensatory increase in glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
97
2
1

Year Published

1982
1982
2005
2005

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 400 publications
(112 citation statements)
references
References 49 publications
12
97
2
1
Order By: Relevance
“…This observation established that the glucagon secretory defect during hypoglycemia in diabetic patients is not due to a global defect in ␣-cell function but rather involves a specific defect in sensing hypoglycemia. Previous studies (20,21) emphasized the importance of the glucagon response during counterregulation of hypoglycemia in humans. Sjoberg et al (22) found that diabetic subjects with…”
Section: Discussionmentioning
confidence: 99%
“…This observation established that the glucagon secretory defect during hypoglycemia in diabetic patients is not due to a global defect in ␣-cell function but rather involves a specific defect in sensing hypoglycemia. Previous studies (20,21) emphasized the importance of the glucagon response during counterregulation of hypoglycemia in humans. Sjoberg et al (22) found that diabetic subjects with…”
Section: Discussionmentioning
confidence: 99%
“…Loss of the glucagon response to hypoglycemia is an important problem for patients with type 1 diabetes and for patients with diabetes who require insulin-based therapy for glycemic control (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Cryer et al (15) attributed loss of the glucagon response in diabetes to an absence of an essential signal from the ␤-cell.…”
mentioning
confidence: 99%
“…In normal man plasma concentrations of the counterregulatory hormones (e. g. adrenaline, glucagon, cortisol and growth hormone) increase in response to insulin-induced hypoglycaemia [1,2]. In normal subjects, glucagon plays a major role in blood glucose recovery after hypoglycaemia [1,31, whereas the role of other counter-regulatory hormones in producing blood glucose recovery has not yet been completely clarified.…”
mentioning
confidence: 99%
“…In normal subjects, glucagon plays a major role in blood glucose recovery after hypoglycaemia [1,31, whereas the role of other counter-regulatory hormones in producing blood glucose recovery has not yet been completely clarified.…”
mentioning
confidence: 99%